Design And Development Of Formalin Levels Detection In Food Based On Arduino Nano Microcontroller Using Fuzzy Method - Eka Rahamadi Susilo; Akim M.H Pardede; Siswan Syahputra (International Journal of Health Engineering and Technology, 2022)
Formalin is very dangerous for human health and for that we need to detect the content of formaldehyde in these foods so that this abuse should be known easily. For that we need a tool that can detect the content of formalin in food. The use of a gas sensor is the fastest way to detect formalin used in food because it does not require a chemical process that is not instant. The MQ-138 sensor is used as a formalin detection sensor in food where this tool uses an Arduino microcontroller as a processor and data processor for the MQ-138 sensor readings which then the sensor readings will be displayed on a 16x2 LCD display, and then the tool system is inputted with a fuzzy method. logic, with fuzzy logic that is safe, a little formalin, and a lot of formalin.